Gestational weight gain charts for twin pregnancies in Southeast China - Lin, Lihua (BMC Pregnancy Childbirth, 2020)
BACKGROUND: To establish age-standardized charts of weight gain for term twin pregnancies in Southeast China. METHODS: We designed a retrospective study on data from women pregnant with twins, a gestational age beyond 36 weeks and an average weight ≥ 2500 g. We established hierarchical linear regression models to express gestational weight gain patterns. RESULTS: We analyzed data from 884 women pregnant with twins (151 underweight, 597 normal weight, and 136 overweight). Our final models fit the crude weight measurement data well. The means of weight gain generally decreased as the pre-pregnancy BMI increased. For each BMI category, the mean weight gains increased with the gestational age and the standard deviation increased slightly. The mean weight gains were 18.82 ± 6.73, 18.53 ± 6.74, and 16.97 ± 6.95 kg at 37 weeks in underweight, normal weight, and overweight women, respectively. CONCLUSION: The weight gain chart can be used to estimate maternal weight gain to be gestational age–standardized z scores by pre-pregnancy BMI and may serve as an innovative tool for perinatal care providers to guide the weight gain of women pregnant with twins.